FIB-4: A screening tool for advanced liver fibrosis in a cohort of subjects participating in a primary care weight-loss program - Victoria Mignot; Odile Fabre; Rémy Legrand; Sébastien Bailly; Charlotte Costentin (PLoS ONE, 2025)
Systematic screening for liver fibrosis using FIB-4 score is recommended in primary care for patients with chronic liver disease risk factors. This study assesses the prevalence and characteristics of patients at risk for advanced fibrosis in a weight loss program. This multicenter retrospective cohort study includes obese and overweight subjects participating in a weight loss program across 110 French centers. 34 510 participants with baseline FIB-4 available were included, predominantly women (78.3%), median age of 54 years, 70% obese. Baseline FIB-4 values were <1.3, 1.3–2.67 or >2.67 in 80.9%, 18.1% and 1% of the participants, respectively. When moving from the lower risk category (<1.3) to the highest (>2.67), the rates of metabolic comorbidities such as diabetes rose (from 3.2% to 13.3%). After 5 (3–7) months, all anthropometric parameters improved. A follow-up FIB-4 value was available in 20.7% participants. Among high-risk, 43% changed classes, 4.6% moving to the lower risk-category.